END2END-подход в задачах автоматического распознования речи - Михайличенко, И. В. (ХНУРЕ, 2020)
Improving the quality and speed of speech recognition in noisy environments by creating a stable intellectual model, based on the application of the end2end approach, which makes it possible to minimize the loss of audio signals.
Keywords: END2END-подход; blank-символ; человек-компьютер